Technological proficiency and online resource utilization in mathematics education: A study of higher education instructors in the Philippines - Ma. Kathleen Mae Geremias Acopio (Jurnal Elemen, 2025)
This study examined the relationship between technological proficiency and online resource utilization among 31 mathematics instructors in higher education institutions (HEIs) in Tacloban City, Philippines. Using a descriptive-correlational design, the research assessed how instructors’ competence in key information and communication technology (ICT) domains—such as word processing, video conferencing, electronic presentations, web navigation, and troubleshooting—correlated with their ability to effectively use online instructional resources. Adapted instruments from (Flores, 2019) and (Das, 2019) were employed to measure online resource utilization and technological proficiency, respectively. Data were analyzed using descriptive statistics and Pearson correlation. Results indicated a significant positive association—though not causal—between overall technological proficiency and online resource use, with document scanning and spreadsheet processing showing statistically significant relationships at the 0.05 level. Notably, eleven participants reported no prior professional development in digital pedagogy, highlighting disparities in readiness. Despite this, most instructors reported moderate to high self-efficacy in utilizing online resources. Ethical protocols were followed, and participation was voluntary. The findings emphasize the need for targeted, ongoing professional development and institutional support to strengthen technology integration in mathematics teaching, particularly in resource-constrained settings like the Philippines.